The Effectiveness of Baamboozle Game as a Learning Media for Flat Geometry in Improving Students' Problem-Solving Skills - Hilda; Prasetyaningtyas, Fitria Dwi (Universitas Pendidikan Ganesha, 2024)
The issue of low mathematical problem-solving abilities among students requires innovative, interactive, and effective learning media. This study aims to develop and implement the Baamboozle game as a mathematical learning media for flat geometry material for fifth-grade students. The study employed the Research and Development (R&D) method with the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. The research subjects consisted of fifth-grade students and teachers. Data were collected through expert validation tests, student response questionnaires, and pretest and posttest assessments. Data analysis was performed descriptively and inferentially to assess the media's feasibility and effectiveness. The results showed that the Baamboozle game was highly feasible for use in learning, based on expert validation with high scores and positive student feedback. Moreover, the use of this game significantly improved students' mathematical problem-solving abilities, as evidenced by the significant increase in posttest scores compared to pretest scores, with a significance level of < 0.001. The conclusion of this study is that the Baamboozle game is effective as a mathematical learning media, particularly for flat geometry material, in enhancing students' problem-solving abilities.